Effect of The Staggering of a Contact Wire on Wear Behaviour in Malaysian Railway Traction Power Supply - Hashim, Hairulazwan; Mohd Ramli, Farah Shuhadah; Othman, Azwan (International Journal of Integrated Engineering, 2024)
With Malaysia’s rapid railway development, resolving the issue of train safety assurance during operation is critical. In advanced railway systems, electricity is transmitted to trains via the sliding contact of the pantograph and overhead catenary system, which leads the transmission wire in the pantograph and catenary system to deteriorate continuously. Monitoring of contact wire wear is essential for ensuring the safety and efficient operation of electric trains in terms of precision and service efficiency. This research has been developed to detect and monitor contact and stagger wire wear. The bottom of a contact wire can be captured using image processing technology using a line sensor camera. The measurement is carried out using the binocular ranging principle by evaluating the local wear conditions captured by two cameras in order to ascertain the complete wear data of the contact wire and the stagger value. The method has been used between chainage M403.680 and M390.1476 Upline, and the inspection data shows that 94.12 % of contact wire wear in the SPK-Serdang section of KVDT Line is distributed in the interval (0 mm - 0.3 mm). The highest wear distribution of the whole line is around 0.3 mm.